The Effectiveness of Implementing Blud at Community Health Centers in Improving the Quality of Health Services - Dini Putri Hapsari Pratiwi; Syahran Syahran (CV Edujavare Publishing, 2026)
Strategic policies that have been proposed include placing community health centers under the auspices of Regional Public Service Agencies (BLUDs), which provide greater flexibility in financial and operational management, thereby enabling improvements in the quality of public health services. This study aims to analyze the effectiveness of implementing the Regional Public Service Agency (BLUD) scheme in community health centers (Puskesmas) to improve healthcare service quality in Bulungan Regency, focusing on UPTD Puskesmas Tanjung Selor. A qualitative approach with a case study design was applied. Data were collected through in-depth interviews, observation, and documentation involving informants from the District Health Office, the Regional Financial and Asset Management Agency (BPKAD), the Head of Puskesmas, BLUD management staff, revenue and expenditure treasurers, activity implementation officers (PPTK), accounting staff, and medical personnel. Data analysis followed the stages of data reduction, data display, and conclusion drawing. The findings indicate that BLUD implementation at Puskesmas Tanjung Selor has generally been effective, as reflected in greater flexibility in financial management, faster procurement of operational needs, and the development of service innovations such as strengthening 24-hour emergency services, procuring ambulances, and independently providing medical equipment. The BLUD scheme also contributed to increased community satisfaction, as shown by the upward trend in the Community Satisfaction Survey (SKM) scores. However, several challenges remain, including limited human resources with sufficient competence in BLUD financial management, increased workload due to multiple roles, procurement constraints (e-catalog/inaproc) caused by limited suppliers, and suboptimal integration of financial reporting systems.